2015
DOI: 10.3390/molecules20034357
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Chapman, E.; et al. Inhibitors of the AAA+ Chaperone p97. Molecules 2015, 20, 3027-3049

Abstract: The authors wish to make the following correction to paper [1], doi:10.3390/molecules20023027, website: http://www.mdpi.com/1420-3049/20/2/3027/. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…One p97 inhibitor, CB‐5083, is currently under investigation in two phase 1 human clinical trials for cancer patients: one in patients with advanced solid tumors (NCT02243917), and the other in patients with relapsed multiple myeloma (NCT02223598). Different classes of p97 inhibitors have been developed, and CB‐5083 is the first p97 inhibitor to enter clinical trials.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…One p97 inhibitor, CB‐5083, is currently under investigation in two phase 1 human clinical trials for cancer patients: one in patients with advanced solid tumors (NCT02243917), and the other in patients with relapsed multiple myeloma (NCT02223598). Different classes of p97 inhibitors have been developed, and CB‐5083 is the first p97 inhibitor to enter clinical trials.…”
Section: Figurementioning
confidence: 99%
“…More than 30 p97 cofactors are known . Although great effort has been taken to screen for p97 inhibitors, and effects of cofactors on p97 have been studied, only recently have the effects of cofactors on the potencies of p97 inhibitors begun to be investigated. We found that inhibition of p97 ATPase activity by ATP‐competitive and D2‐selective p97 inhibitors, ML240 and ML241, is drastically changed by p47, a major p97 cofactor.…”
Section: Figurementioning
confidence: 99%
“…A number of systematic comparisons of foreground mitigation methods have been performed. Chapman et al (2015) compared foreground subtraction methods and found that GMCA proves the most robust to realistic foreground spectra. Alonso et al (2015a) unified a number of subtraction methods under a common mathematical framework and showed that for a large suite of fast simulations the methods perform comparably.…”
Section: Discussionmentioning
confidence: 99%
“…The most well-known implementations of this approach are fast independent component analysis (Chapman et al 2012) and generalised morphological component analysis (GMCA;Chapman et al 2013). The latter appears to be the most robust approach in the foreground subtraction category (Chapman et al 2015) and has been used as part of the LOFAR EoR pipeline (Patil et al 2017).…”
Section: Foreground Subtractionmentioning
confidence: 99%
“…So far, several inhibitors have been reported to inhibit VCP function (30,31). Previously, Sasazawa et al (20) showed that xanthohumol is a VCP inhibitor by binding to the N-terminal domain of VCP.…”
Section: Inhibitor Of Vcp-dependent Fibroblast Migrationmentioning
confidence: 99%